Analisa Sensitivitas Parameter - Parameter Yang Mempengaruhi Rencana Anggaran Biaya (RAB) Perumahan Cluster Di Pekanbaru (Studi Kasus Perumahan Sari Residence) - Luse Benita; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pekanbaru is one of the provincial capital in Indonesian that has rapid population growth about 4%  each year. One of thedevelopment thing is the rapidly growing field of building construction, especially in the field of housing.  Free trade competition in which the selling price as set by the government.  It is necessary to identify the parameters that affect the Budget Plan (RAB) in Type of Cluster House development.  Sensitivity analysis is needed to determine how sensitive a decision to change the parameters that influence it.  Criteria of the largest costs incurred is the cost of home work better than the average yield response of respondents as well as seen from the calculation of the RAB. RAB calculations obtained percentage of the cost of homework on the overall total cost for one (1) of housing units is 61.64%. Retrieved parameters that affect as many as 12 parameters namely: Wall Working, Roof Working, foundation working, concrete working, vast excess soil, deed of sell, Building Permits, Ownership Certificate, Electrical installation, Water Treatment Plan, Mainroad. So we need antisipasif action against these parameters. Keywords: Developer, Budget Plan (RAB), Type of Cluster House, Sensitivity